Obstructive Sleep Apnea in Pregnant Women: A Review of Pregnancy Outcomes and an Approach to Management. Issue 1 (March 2019) - Dominguez, J.E.; Krystal, A.D.; Habib, A.S.
Abstract : ( Anesth Analg . 2018;127:1167–1177) Sleep-disordered breathing (SDB) is often comorbid with obesity; among obese pregnant women, 15% to 20% have obstructive sleep apnea (OSA), and prevalence increases with body mass index (BMI). Untreated OSA has been associated with a range of cardiovascular, pulmonary, and metabolic comorbidities. The authors of this review discussed pregnancy as a vulnerable period for the development or worsening of OSA, associations between OSA and adverse maternal and fetal outcomes, current screening modalities for OSA in pregnancy, and current recommendations regarding peripartum management of OSA.